2015
DOI: 10.1186/s11671-015-1030-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photovoltaic Performance of Dye-Sensitized Solar Cells by Efficient Near-Infrared Sunlight Harvesting using Upconverting Y2O3:Er3+/Yb3+ Phosphor Nanoparticles

Abstract: We report the efficiency enhancement in dye-sensitized solar cells (DSSCs) using Er3+/Yb3+-co-doped Y2O3 (i.e., Y2O3:Er3+/Yb3+) phosphor nanoparticles, prepared by a simple and cost-effective urea-based homogeneous precipitation method, for efficient near-infrared (NIR) sunlight harvesting. Under the light excitation at a wavelength of 980 nm, the as-prepared samples exhibited strong upconversion emissions at green and red visible wavelengths. To investigate the influence of Y2O3:Er3+/Yb3+ nanoparticles on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Finally, CE is an electrocatalytic activation layer deposited on a conductive glass, which is typically a platinum (Pt) film deposited with a fluorine-doped tin oxide (FTO) glass. Until recently, many scientists focused on the performance improvement of the WE for the efficient sunlight harvesting [ 4 6 ]. However, CE also plays an important role in DSSCs; there are three major functions of the CE in DSSCs: (1) transfer electrodes to make the cell as a complete circuit, (2) regenerate the I 3 − in the interface of the electrolyte/CE, and (3) reduce the I − /I 3 − redox couples in order to keep low potential to minimize energy losses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, CE is an electrocatalytic activation layer deposited on a conductive glass, which is typically a platinum (Pt) film deposited with a fluorine-doped tin oxide (FTO) glass. Until recently, many scientists focused on the performance improvement of the WE for the efficient sunlight harvesting [ 4 6 ]. However, CE also plays an important role in DSSCs; there are three major functions of the CE in DSSCs: (1) transfer electrodes to make the cell as a complete circuit, (2) regenerate the I 3 − in the interface of the electrolyte/CE, and (3) reduce the I − /I 3 − redox couples in order to keep low potential to minimize energy losses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, solar conversion efficiency was enhanced in DSSCs containing RE ions as compared with DSSCs lacking RE ions. The authors reported that Tm 3+ /Yb 3+ ions act as luminescence medium and transfer infrared light into visible light through an upconversion luminescence process, which leads to improvement in incident light harvesting as well as enhanced photocurrent of RE‐doped DSSCs. In 2017, Fouad et al reported that with increasing Eu doping concentration optical absorption/fluorescence was enhanced and this resulted in an increase in the FWHM of peaks as well as photoconversion efficiency . It is observed that photoanode layer of Eu‐doped TiO 2 enhances efficiency as compared to undoped TiO 2 and this important property of doping plays an important role in altering the material for DSSCs to exhibit better performance .…”
Section: Re‐doped Tio2 For Spectral Conversionmentioning
confidence: 99%
“…White light can be obtained by not only mixing the appropriate ratio of the three primary red, green, and blue colors, but also by creating the appropriate mixture of blue and yellow emissions [4][5][6][7][8]. Rare earth (RE) ions are often applied in various fields such as field-emission displays (FED), temperature sensor and solar cell ions for their promising applications in solidstate multicolor [9][10][11][12]. Among the RE ions, Dy 3 þ ion has attracted much attention because of its white light emission [13,14].…”
Section: Introductionmentioning
confidence: 99%